Is emerging foreign exchange market efficient? / Soofiyah Aiman Sanadi and Bee-Hoong Tay - Aiman Sanadi, Soofiyah; Bee, Hoong Tay (Universiti Teknologi MARA, Kedah, 2021)
This study examines the weak form efficiency in the eight selected Asian foreign exchange markets from January 2010 to September 2020. The selected foreign exchange markets are Malaysia, India, Pakistan, China, Taiwan, Thailand, South Korea, and Indonesia. Augmented Dickey-Fuller (ADF) test, Phillips-Perron (PP) test and Kwiatkowski, Phillips, Schmidt, and Shin (KPSS) test are adopted to investigate the weak form efficiency. The outcomes for all tests indicated that all the selected foreign exchange markets were weak form efficient except Taiwan when tested with the KPSS test. These findings have important implication to investors, fund managers and policy makers.